DECOMPOSITION OF KYANITE AND SOLUBILITY OF AL2O3 IN STISHOVITE AT HIGH PRESSURE AND HIGH TEMPERATURE CONDITIONS - Liu X.; Nishiyama N.; Sanehira T.; Inoue T.; Higo Y.; Sakamoto S. (My University, 2006)
In order to constrain the high-pressure behavior of kyanite, multi-anvil experiments have been carried out from 15 to 25 GPa, and 1,350 to 2,500°C. Both forward and reversal approaches to phase equilibria were adopted in these experiments. We find that kyanite breaks down to stishovite + corundum at pressures above ~15 GPa, and stishovite + corundum should be the stable phase assemblage at the pressure-temperature conditions of the transition zone and the uppermost part of the lower mantle of the Earth, in agreement with previous multi-anvil experimental studies and ab initio calculation results, but in disagreement with some of the diamond-anvil cell experimental studies in the literature. The Al2O3 solubility in nominally dry stishovite has been tightly bracketed by forward and reversal experiments; it is slightly but consistently reduced by pressure increase. Its response to temperature increase, however, is more complicated: increases at low temperatures, maximizes at around 2,000°C, and perhaps decreases at higher temperatures. Consequently, the Al2O3 solubility in dry stishovite at conditions of high temperature-high pressure is very limited. © Springer-Verlag 2006.
Keywords: AL2O3 SOLUBILITY IN STISHOVITE; CORUNDUM; KYANITE; PHASE EQUILIBRIUM; STISHOVITE